Toxicity and enzymatic activity changes in rice weevil (Sitophilus oryzae) induced by basil (Ocimum basilicum) and cumin (Cuminum cyminum) essential oils - Ahmed Fayez Omar; Fatma Mohamed Ameen Khalil; Maryam M. Alomran; Tamer Ismail; Ahmed I. El-Tokhy; Khaled Abdelaal; Fatehia N. Gharsan; Reem Nasser Almozini; Ahmed M. Abouelatta (Scientific Reports)
Abstract The rice weevil Sitophilus oryzae is one of the primary insects that infest stored grains, causing both quantitative and qualitative losses. The use of synthetic pesticides to control it has led to the emergence of several problems related to human health and the environment, which has prompted the search for safer alternatives for their control. In this study, the effectiveness of two essential oils, cumin (Cuminum cyminum) and basil (Ocimum basilicum), was evaluated as insecticides for controlling the rice weevil at three different times intervals and various concentrations. (GC-MS) analysis revealed that both oils contain several key compounds, such as procanal (26.07%), ˠ- terpinene (15.78%), for C. cyminum and linalool (56.7%), cadinol, epi-α (11.4%) for O. basilicum, in addition to some secondary components. The results showed that, the lethal concentration (LC50) of cumin was 49%, 45%, and 33% lower than that of basil at the 24, 48, and 72-h assessment periods, respectively demonstrating the superiority of cumin over basil. Regarding the effects on the levels of certain enzymes activity, the results indicated that both oils had a significant impact on the activity of both enzymes ALP and GOT, while there was no significant effect on (GOT), α-amylase, and acetylcholinesterase (AChE) compared to control. Based on the obtained results, it can be concluded that tested essential oils could be developed as a safe and effective alternatives for controlling rice weevil.